STRATEGI KEPALA DESA DALAM MENINGKATKAN KESADARAN MEMBAYAR ZAKAT MELALUI PROGRAM KAMPUNG ZAKAT DI DESA SULUNG KECAMATAN SEJANGKUNG TAHUN 2023 - Eliyani Eliyani; Susilawati Susilawati; Rona Rona (MUSHAF JOURNAL: Jurnal Ilmu Al Quran dan Hadis, 2024)
The aim of this research is to describe and find out about: 1) the strategies used by village heads in increasing awareness of paying zakat in Sulung village, Sejangkung District with the Zakat Village program, 2) the obstacles faced by village heads in increasing awareness of paying zakat in Sulung village, Sejangkung District. through the Zakat Village program. This research uses a qualitative approach and the type of research used is descriptive. The data collection techniques used were observation, interviews and documentation. Then the data analysis techniques used in this research are data reduction, data presentation, data verification and drawing conclusions. Meanwhile, techniques for checking the validity of research data use: triangulation, member check. The results of this research show that: 1) The village head's strategy in increasing awareness of paying zakat in Sulung village is by a) the formulation stage related to several preparations that must be made by the village head when implementing a strategy, b) implementation, the village head conveys and implementing the draft strategy that has been made to the community, including implementing the Zakat Village program, c) evaluation, at this stage the village head conveys the results of monitoring that has been carried out by BAZNAS regarding problems or obstacles found during the implementation of the Zakat Village program. 2) Supporting and inhibiting factors for village heads in increasing awareness of paying zakat through the Zakat Village program in Sulung village, Sejangkung subdistrict are, supporting factors include: a) assistance from LAZ (Lembaga Amil Zakat) including educational, economic and health assistance, b) community support local, c) cooperation between regional government and village government. Meanwhile, inhibiting factors include: a) the geographical conditions of Sulung village, b) people who do not fully understand zakat, c) inadequate road access to Sulung village.